An experiment on individual ‘parochial altruism’ revealing no connection between individual ‘altruism’ and individual ‘parochialism’ - Corr, Philip J.; Hargreaves Heap, Shaun P.; Seger, Charles R.; Tsutsui, Kei (Frontiers in Psychology, 2015)
Is parochial altruism an attribute of individual behaviour? This is the question we address with an experiment. We examine whether the individual pro-sociality that is revealed in the public goods and trust games when interacting with fellow group members helps predict individual parochialism, as measured by the in-group bias (i.e., the difference in these games in pro-sociality when interacting with own group members as compared with members of another group). We find that it is not. An examination of the Big 5 personality predictors of each behaviour reinforces this result: they are different. In short, knowing how ‘nice’ individuals are with respect to fellow group members does not help predict their parochialism.